Geographic Information System for Mapping Solar Power Plants in Lolo Wano Village - Haryance Umbu Dasa; Friden Elefri Neno; Alexander Adis (novamindpress, 2025)
The use of renewable energy, particularly solar power plants (SPPs), is one of the strategic solutions to overcome limited access to electricity in rural areas. Lolo Wano Village, as one of the villages with high solar radiation intensity, has great potential for SPP development. However, the planning of SPP construction is often hampered by a lack of integrated spatial data related to residential locations, public facilities, and land availability. This study aims to design a Geographic Information System (GIS) capable of mapping the potential and determining strategic coordinates for SPP construction in Lolo Wano Village. The research method was conducted by collecting primary data in the form of GPS coordinates of residents' houses, schools, village offices, and vacant land with potential for use. Secondary data included administrative maps, topographic maps, and solar radiation data from BMKG and global sources. The data was processed using QGIS/ArcGIS software through the stages of map digitization, spatial overlay, and land suitability analysis based on criteria of solar radiation, accessibility, land area, and proximity to residential areas. The results of the study show that the use of GIS can produce digital maps of the distribution of existing solar power plant locations as well as recommendations for new locations suitable for development. This system not only assists village governments in making decisions on renewable energy development, but also supports equitable access to electricity for the community. Thus, the application of GIS in mapping solar power plants in Lolo Wano Village plays an important role in supporting sustainable development and improving the quality of life of the local community.